Feminized Water Geographies: Harnessing Urban Design Principles as a response to the water needs of women living in the informal settlement known as Gabon, Daveyton - Mogola, Itumeleng (University of the Witwatersrand, Johannesburg, 2024)
Feminized water geographies is a concept concerned with the improvement of the livelihoods of women living in urban contexts of water scarcity such as informal settlements (Dixon & Jones, 2006). The complexity of the concept cannot be reduced to a single theoretical thread but is understood and investigated through the understanding that the relationship between women and water is complex and is defined through four theories namely, the Feminization of water which advocates for women’s access to clean and safe water while reducing the laborious tasks that limit their economic, social, and political participation. Secondly, African Ethnographies explores African culture and Black African female identities and the resultant vocabularies and expressions of surviving urban informality, thirdly, urban informality begins to spatialise the water responsibilities of women that occur within contexts of resource deprivation which has an impact on a woman’s urban experience of accessing water. Lastly, the theory of Feminist Geographies strives to improve the livelihoods of women by unpacking the urban, social, cultural, and economic landscape that women have to navigate to survive (Dixon & Jones, 2006). As a result, the need to address the precarious conditions of informal settlements within water-scarce contexts to try to create urban environments that are responsive and sensitised to women’s water needs is important and forms the crux of the research. By harnessing urban design principles including water-sensitive urban design principles that address the spatial implications of water scarcity in contexts of urban informality while being sensitised to women’s needs, the research can begin to explore and answer the possibilities of creating sustainably inclusive spaces.
A thesis submitted to the Master of Urban Design to the University of the Witwatersrand, Johannesburg, in the Faculty of Engineering and Built Environment, School of Architecture and Planning, in 2024,
Keywords: Feminised Water Geographies; Women living in urban; Water scarcity; Economic, social, and political participation; Urban, social, cultural, and economic landscape; UCTD; SDG-5: Gender equality